Tax Amnesty and Earnings Management: An Initial Evidence - Geraldina, Ira; Jasmine, Rania (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
The aim of this paper is to examine the effect of earnings management on the participation of company owners in tax amnesty program in Indonesia. This study uses a matching sample approach that consist of publicly listed companies that participated in tax amnesty program and companies that did not participate in tax amnesty program during 1 July-30 September 2016. The final sample was obtained 339 firm years. Information about the owner of the company that participated the tax amnesty program was obtained from the mass media. The results show that accrual earnings management has a positive effect on the possibility of the owner of the company to participate in the tax amnesty program. This study suggests the users of financial reports to pay attention on the level of aggressiveness of companies’ earnings management whom the owners participate in tax amnesty program. The aggressive financial reporting could indicate the low quality of the financial reporting. This study also provides conceptual contribution to the development of science regarding the relation of earnings management and the probability of a company owners participating in the tax amnesty program.